2022
DOI: 10.1021/acs.nanolett.2c03598
|View full text |Cite
|
Sign up to set email alerts
|

eg Occupancy as a Predictive Descriptor for Spinel Oxide Nanozymes

Abstract: Functional nanomaterials offer an attractive strategy to mimic the catalysis of natural enzymes, which are collectively called nanozymes. Although the development of nanozymes shows a trend of diversification of materials with enzyme-like activity, most nanozymes have been discovered via trial-and-error methods, largely due to the lack of predictive descriptors. To fill this gap, this work identified e g occupancy as an effective descriptor for spinel oxides with peroxidaselike activity and successfully predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Copyright 2019 Springer Nature. Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Computing-driven Guided Design Of Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2019 Springer Nature. Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Computing-driven Guided Design Of Nanozymesmentioning
confidence: 99%
“…In addition, they plotted volcano maps of the specific activity of nanozymes and the occupancy of the e g orbitals and successfully predicted the highest POD-like activity of the spinel oxide LiCo 2 O 4 (Figure 3F), which exhibited more than 1 order of magnitude increase in the catalytic activity compared to the highest POD-like activity of ZnCo 2 O 4 in the spinel ZnB 2 O 4 series. 43 The above studies have demonstrated the ability of e g to accurately predict the POD-like activity of spinels and chalcogenides. As a material electronic structure descriptor, e g has a high potential for the prediction of other types of materials.…”
Section: Computing-driven Guided Design Of Nanozymesmentioning
confidence: 99%
“…In addition, studies have revealed that the catalytic activity of spinel oxides for the oxygen reduction reaction (ORR) strongly relies on the occupancy of the e g orbitals of the transition metal cations at the octahedral (O h ) sites. The transition metal e g orbitals exhibit significant overlap with the O 2p orbitals of the oxygen-related adsorbates. By achieving a moderate e g ≈ 1.0 configuration at the O h sites, the ORR/OER activity can be optimized by balancing the binding strength of oxygen intermediates involved in various rate-determining steps. , This modification facilitates the adsorption of O 2 and the dissociation of OH – , leading to enhanced ORR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Among enzyme mimics, spinel oxides (AB 2 O 4 ) have a well-defined but tunable crystal structure with two sites, octahedral (Oh) and tetrahedral (Td) sites, and the distribution of cations in two sites determines its catalytic efficiency. In general, the Oh sites play a primary role during the catalytic reaction because they are preferentially exposed on the near-surface, and a shorter distance between Oh–Oh sites accelerates the reaction kinetics. Currently, most studies were primarily focused on modulating Oh metal ion species and valence states to enhance their catalytic efficiency. For example, modulating the Oh site cations could regulate the peroxidase-mimicking activity of ZnB 2 O 4 (B = Cr, Mn, Fe, and Co) . The highest catalytic activity was observed when the Co cations occupied the Oh site.…”
Section: Introductionmentioning
confidence: 99%
“…For example, modulating the Oh site cations could regulate the peroxidase-mimicking activity of ZnB 2 O 4 (B = Cr, Mn, Fe, and Co). 21 The highest catalytic activity was observed when the Co cations occupied the Oh site. Using ZnMn 2 O 4 as a model material, the effect of Mn valence at Oh sites on its multiple antioxidant activities was explored.…”
Section: ■ Introductionmentioning
confidence: 99%